2019
DOI: 10.3390/jcm8091499
|View full text |Cite
|
Sign up to set email alerts
|

An Early, Universal Mediterranean Diet-Based Intervention in Pregnancy Reduces Cardiovascular Risk Factors in the “Fourth Trimester”

Abstract: An early antenatal dietary intervention could play an important role in the prevention of metabolic diseases postpartum. The aim of this study is to evaluate whether an early, specific dietary intervention reduces women’s cardiovascular risk in the “fourth trimester”. This prospective cohort study compares 1675 women from the standard-care group (ScG/n = 676), who received standard-care dietary guidelines, with the intervention group (IG/n = 999), who received Mediterranean diet (MedDiet)-based dietary guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…These authors indicate that the length of the food supply chain is a key determinant of the risk of MetS in the population living on a Mediterranean diet [30]. Furthermore, the study conducted by Assaf-Baut et al among women with and without gestational diabetes mellitus (GDM) in the 12th-14th week after childbirth shows that the intervention on diet reduced the relative risk of MetS, but not the risk of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 97%
“…These authors indicate that the length of the food supply chain is a key determinant of the risk of MetS in the population living on a Mediterranean diet [30]. Furthermore, the study conducted by Assaf-Baut et al among women with and without gestational diabetes mellitus (GDM) in the 12th-14th week after childbirth shows that the intervention on diet reduced the relative risk of MetS, but not the risk of insulin resistance [31].…”
Section: Discussionmentioning
confidence: 97%
“…The MedDiet enriched with EVOO and pistachios has been associated with health benefits in the mother [25,30,31]. There are also suggestions that these benefits can be transferred to postnatal life [32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our group has shown that an early adherence to a MedDiet-supplemented with extra virgin olive oil (EVOO) and nuts-in pregnancy can reduce the risk of GDM and other adverse materno-fetal outcomes [23,24]. It has also been associated with a better postpartum metabolic profile in the mother [25]. Whether these benefits are conveyed to the offspring, remains to be known.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with DM2, OO supplementation reduces HbA1c, fasting plasma glucose and inflammatory biomarkers, compared to controls [380]. In addition, MedDiet and MedDiet + EVOO + nuts reduce metabolic syndrome and insulin resistance in the postpartum [394,395]. Indeed, a systemic review and meta-analysis, which includes RC trials that examine lipid profile, inflammation, and oxidative stress biomarkers in individuals that consume low MPC OO and high MPC OO, observed the improvement in MDA, oxLDL, Chol, and HDL.…”
mentioning
confidence: 99%